2003
DOI: 10.1034/j.1600-0579.2002.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing communication skills for medical interviews in a postgraduate clinical training course at Hiroshima University Dental Hospital

Abstract: The study was conducted to investigate and clarify the effectiveness of our method of teaching communication and interview skills for medical interviews. Subjects were 18 first-year residents, enrolled in a postgraduate clinical training course at Hiroshima University Dental Hospital. Subjects underwent two objective structured clinical examinations (OSCEs), and the results of instructor and resident assessments of various elements dealing with necessary communication skills for conducting medical interviews w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Two studies’ authors argued that these methods could be used in both clinical and preclinical years of study, as they had proved valuable for knowledge acquisition and understanding 7 , 28 . Role‐playing, patient interviewing, and clinical observation were discussed in teaching communication skills especially in the clinical years of dental study 6 , 24 27 , 29 . Two studies found these methods were useful in distinguishing effective from ineffective communication skills, and dental students showed positive attitudes toward learning such skills 13 , 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies’ authors argued that these methods could be used in both clinical and preclinical years of study, as they had proved valuable for knowledge acquisition and understanding 7 , 28 . Role‐playing, patient interviewing, and clinical observation were discussed in teaching communication skills especially in the clinical years of dental study 6 , 24 27 , 29 . Two studies found these methods were useful in distinguishing effective from ineffective communication skills, and dental students showed positive attitudes toward learning such skills 13 , 30 .…”
Section: Resultsmentioning
confidence: 99%
“…There was wide variation in assessment measures in the included articles. Some authors applied widely used measures like the objective structured clinical examination (OSCE), 29 , 34 written assessments, 35 reflective exercises, 26 , 28 , 32 , 35 role‐playing, 35 direct observation, 24 , 26 , 32 self‐assessment, 24 , 25 , 32 and patient feedback 27 , 28 , 32 , 36 . Others applied new assessment instruments that had been validated in other areas of health professions education, like the Calgary‐Cambridge concept (CCOG), 6 the behavioral observation rating scale, 31 the Communication Skills Attitude Scale (CSAS), 25 the Masters Interview Rating Scale (MIRS), 37 and the Arizona Clinical Interviewing Rating (ACIR) 10 , 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Also used in dental education to evaluate communication skills [103], [104], problem-solving skills, and critical thinking [105]. …”
Section: Discussionmentioning
confidence: 99%
“…Mandatory internship in a postgraduate clinical training course will be required for new dentists in Japan starting in 2006. [18][19][20][21][22][23][24] In terms of cognitive level, a limitation of the information reported in this article is that the validity of item classification was not established because the number of people who have completed both the NBDE and the NED is small. Thus, some items (6.3 percent) were impossible to classify.…”
Section: Discussionmentioning
confidence: 99%